The effect of pyruvate on the development and progression of post-stroke depression: A new therapeutic approach - Frank, Dmitry (Neuropharmacology, 2019)
Post-stroke depression (PSD) is a common and serious complication following stroke. Both stroke and depression have independently been associated with pathologically elevated glutamate levels in the brain’s extra-cerebral fluid (ECF). Here we evaluate an alternative therapeutic approach to PSD with pyruvate. Rats were randomly assigned into one of 3 groups: Middle Cerebral Artery Occlusion (MCAO) plus pyruvate treatment, MCAO plus placebo treatment, and sham operated rats. Post-MCAO depressive and anxiety-like behavior was assessed, along with neurological status, brain infarct zone, brain edema, blood brain barrier (BBB) breakdown, cerebrospinal fluid and blood glutamate levels. Anxiety-like behavior and levels of blood alanine and α-ketoglutarate were measured in naïve rats treated with pyruvate, as a control. Post-stroke neurological deficit with concurrent elevation in glutamate levels were demonstrated, with peak glutamate levels 24 h after MCAO. Treatment with pyruvate led to reduced glutamate levels 24 h after MCAO and improved neurologic recovery. Pyruvate treatment reduced lesion volume, brain edema and the extent of BBB permeability 24 h post-MCAO. Naïve rats treated with pyruvate showed increased levels of α-ketoglutarate. Rats demonstrated post-stroke depressive behavior that was improved by the administration of pyruvate. There was less anxiety-like behavior in post-stroke rats treated with placebo in comparison to the post-stroke rats treated with pyruvate or sham operated rats. Glutamate scavenging with pyruvate appears to be an effective as a method in providing neuroprotection following stroke and as a therapeutic option for the treatment of PSD by reducing the consequent elevations in CNS glutamate levels.